Role of survivin phosphorylation by aurora B in mitosis - Delacour-Larose, Marlène (Landes Bioscience, 2007)
The chromosomal protein passenger complex, a key mitotic regulator, consists of at least four proteins, INCENP, Aurora B, Survivin and Borealin. Survivin, in contrast to the other members of the chromosomal protein passenger complex (CPC), is mobile at metaphase. This protein is also phosphorylated by Aurora B at Threonine 117. In this work we have studied the role of the phosphorylation of Survivin in mitotosis by using non phosphorylable T117A and phosphomimic T117E silent resistant Survivin mutants, inducible cell lines expressing these mutants and a combination of siRNA, time-lapse microscopy and FRAP analysis. Time lapse microscopy and FRAP analysis show that Survivin T117A mutant is very stably associated with centromeres and its expression induces a prometaphasic arrest in endogenous survivin depleted cells. In addition, Survivin T117A was unable to rescue the phenotypes of the endogenous survivin depleted cells. Expressed in these cells, the phosphomimic Survivin T117E mutant exhibits a very weak interaction with the centromeres and behaves as a dominant negative mutant inducing severe mitotic defects. Our data suggest that the Aurora B generated phosphorylation/dephosphorylation cycle of Survivin is required for proper proceeding of mitosis.